Bibliometric Analysis of 20-Year Development of Waqf Research in Indonesia Using VosViewer - Wiranda Wulandari; Nil Firdaus (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
This study aims to describe the 20 years of development of scientific publications in the field of waqf from 20004 to 2023, so that in the future it will provide the results of this research that have an impact on the search for the latest research topics. Therefore there are two identified topics that will be discussed in this study, the first is to find out the development of waqf publications in Indonesia in 2004-2023. secondly to find out the existence of scientific publications about waqf in Indonesia based on keywords and authors. From the results of the research, the first shows that there are 970 Google Scholar indexed articles using the Publish or Perish application. Writings published on Google Schooler were abundant in 2016-2017. There are 10 prolific authors during the 20 years of the development of scientific publications about waqf and have the most citations with a total of 253. Second, the existence of scientific publications about waqf in Indonesia is based on keywords, namely the keywords of waqf objects that have been published the most in 20 years. For this reason, through this research we can also find out the topic of waqf, this can make it easier for future writers to determine the theme according to the current novelty about waqf, starting from the potential and opportunities of waqf in the modern era, management of cash waqf, distribution of waqf and so.